V. 10 (New Delhi, 1989)
The basis for this Constitution is federal in structure. I hold the opinion that centrifugal forces will become so strong that the process of amendment will have to be resorted to order to change this Constitution. We take into consideration the political facts of our life. With this background must in view article 306 ought to be modified. My amendment is very reasonable. In the concluding portion of article 306 it has been said that all laws passed under this article to the extent to which they are inconsistent with the main provisions of this Constitution will cease to operate. I think this is unneces sary and undesirable. The work of centralization which will be achieved within five years should not be undone. The provincial Governments must accept the laws passed within this period of five years or fifteen years if the House accepts my amendment. The scope of article 306 is also limited from another point of view. We have given powers to Parliament to deal with production, supply and distribution etc., of these commodities. The entire gamut of these subjects ought to have been brought within the purview of the Government of India. Why this limited sphere? This limited power is not desirable. I think fissiparous forces ought to be circumvented if we are to become a powerful nation.
Keywords: Legislative bodies - India debates 1948